2011
DOI: 10.1007/s11250-011-9803-7
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Moringa oleifera fresh or ensiled to dairy cows—effects on milk yield and milk flavor

Abstract: Moringa oleifera, either fresh or ensiled, was compared with Elephant grass as a main feedstuff for dairy cows. To test the effects feed had on milk yield, milk composition, ration digestibility, and the organoleptic characteristics of milk, six lactating dairy cows were used in a Changeover 3 × 3 Latin Square experiment, replicated twice. With equal intake of metabolizable energy the intake of protein and fiber differed (p < 0.001) between all diets where fresh Moringa had the highest and the Elephant grass d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 21 publications
2
25
0
7
Order By: Relevance
“…Esto puede ser explicado porque el contenido de nitrógeno en las hojas y tallos jóvenes generalmente no disminuye significativamente cuando la madurez de la planta incrementa en rangos de edades muy cortas (Miquilena et al, 1995). En el presente trabajo el contenido de PB estuvo entre el rango de 170-274 g PB kg -1 MS, reportado por otros autores (Reyes-Sánchez et al, 2006a;Reyes-Sánchez et al, 2006b;Reyes-Sánchez et al, 2009;Mendieta-Araica et al, 2011;Mendieta -Araica et al, 2013) No obstante, el contendido de FDN, FDA y cenizas incrementan ligeramente cuando se incrementa la edad de rebrote. Los tallos jóvenes son normalmente de alta calidad, sin embargo, la calidad disminuye más rápido que en las hojas, debido a que la pared celular y el contenido de lignina aumentan al incrementar la edad de rebrote.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…Esto puede ser explicado porque el contenido de nitrógeno en las hojas y tallos jóvenes generalmente no disminuye significativamente cuando la madurez de la planta incrementa en rangos de edades muy cortas (Miquilena et al, 1995). En el presente trabajo el contenido de PB estuvo entre el rango de 170-274 g PB kg -1 MS, reportado por otros autores (Reyes-Sánchez et al, 2006a;Reyes-Sánchez et al, 2006b;Reyes-Sánchez et al, 2009;Mendieta-Araica et al, 2011;Mendieta -Araica et al, 2013) No obstante, el contendido de FDN, FDA y cenizas incrementan ligeramente cuando se incrementa la edad de rebrote. Los tallos jóvenes son normalmente de alta calidad, sin embargo, la calidad disminuye más rápido que en las hojas, debido a que la pared celular y el contenido de lignina aumentan al incrementar la edad de rebrote.…”
Section: Resultados Y Discusiónunclassified
“…Los tallos jóvenes son normalmente de alta calidad, sin embargo, la calidad disminuye más rápido que en las hojas, debido a que la pared celular y el contenido de lignina aumentan al incrementar la edad de rebrote. El contenido de FDN y FDA obtenidos en este estudio para diferentes edades de rebrote están dentro del rango de 219-564 g kg -1 MS y 114-515 reportados por otros investigadores (Makkar and Becker 1996;Makkar and Becker 1997;Reyes-Sánchez et al, 2006;Reyes-Sánchez et al, 2009;Mendieta-Araica et al, 2011;Mendieta-Araica et al, 2013) para FDN y FDA, respectivamente.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Lactose and protein concentrations in milk were not affected by including moringa in their feed, probably because the basal diet provided adequate levels of fibre and protein. 24 Conversely, Mendieta-Araica et al 6 reported a decrease in milk yield without an effect on milk composition when soybean meal was replaced with a moringa leaf preparation in dairy cow feed, which probably correlated with increases in protein and energy intake in the soybean meal concentrate. Kholif et al 8 found that the milk lactose content significantly increased, but the milk-fat and protein concentrations were unaffected when a moringa leaf supplement was included in the feed of lactating goats.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the interest has been increased towards the utilization of moringa (Moringa oleifera) leaves meal as a good protein source in the diets of farm animals as asubstitutefor the traditional protein sources such as soya bean, sunflower and ground nut meals (Sarwatt et al, 2002;Asaolu et al, 2009;Fadiyimu et al, 2010;Mendieta-Araica et al, 2011;El Tazi, 2014;Melesse et al, 2011 andGhomsi et al, 2017) in order to decrease the feeding costs. Sarwatt et al, (2004) reported that moringa foliage is a potential inexpensive protein source for livestock feeding.…”
Section: Intoductionmentioning
confidence: 99%